Nilai Dan Fungsi Mantra dalam Ritrual Purung Ta Liang Marapu Kabupaten Sumba Tengah Nusa Tenggara Timur (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the values and functions of matra (sacred chants) in the Purung Ta Liang ritual, a key element of the Marapu belief system in Central Sumba Regency, East Nusa Tenggara. The ritual plays a significant role in the spiritual life of the Sumbanese people, particularly in maintaining the relationship between humans, ancestors, and the cosmos. The aim of this research is to identify, describe, and analyze the forms of matra used in the ritual, as well as the cultural values and social functions embedded within them. This research employs a qualitative-descriptive method with an ethnographic approach. Data were collected through participant observation, in-depth interviews with traditional leaders, and field documentation. Thematic analysis was conducted, focusing on linguistic structure, symbolic meaning, and the performative context of the matra.The findings reveal that the matra in the Purung Ta Liang ritual functions not only as a medium of communication with ancestral spirits but also contains philosophical, spiritual, and social values such as reverence for nature, community solidarity, and adherence to customary law. The functions of matra include religious, educational, and integrative roles that strengthen the cultural identity of the Sumbanese people. Thus, matra is not merely oral text but also a medium for preserving local knowledge and cultural identity passed down through generations.